BATTERY NEGATIVE ELECTRODE ACTIVE MATERIAL LIQUID AND BATTERY POSITIVE ELECTRODE ACTIVE MATERIAL LIQUID, AND METHOD FOR PREPARING SAME - HOSOBUCHI Kaoru; NAKAI Takayuki; MATSUURA Hiroaki; HAMANA Hiroshi (2017)
The present invention addresses the problem of providing a battery negative electrode active material liquid and battery positive electrode active material liquid, and a method for preparing the same, the liquids being not limited to a specific vanadium concentration or a specific concentration of sulfur in the form of a hydrogen sulfate radical, for example, wherein, even when vanadium in particular has a high concentration, complexes in the liquids do not readily transition to a precipitation type vanadium compound, the liquids maintaining sufficient electrode reactivity and flowability under a free charging/discharging operation, and enabling stable and energy- efficient charging and discharging. The battery negative electrode active material liquid comprises a liquid containing a sulfuric acid acidic vanadium compound, the battery negative electrode active material liquid being characterized by the use of a carbon electrode which contains bivalent and trivalent vanadium and in which a half-value width of a 002 diffraction peak according to X-ray diffraction analysis is not more than 2.5°, wherein a plurality of oxidation waves of bivalent vanadium is detected as observed by a potential sweep method in which, with the electrode and the battery negative electrode active material liquid kept stationary, a potential is swept from a potential on the negative side of -0.1 V with reference to a standard hydrogen electrode potential toward the positive side. La présente invention traite le problème consistant à fournir un liquide de matériau actif d'électrode négative de batterie et un liquide de matériau actif d'électrode positive de batterie, et un procédé de préparation de ceux-ci, les liquides n'étant pas limités à une concentration spécifique de vanadium ou à une concentration spécifique de soufre sous la forme d'un radical sulfate d'hydrogène, par exemple. Même lorsque le vanadium en particulier a une concentration élevée, des complexes dans les liquides ne réalisent pas facilement une transition vers un composé de vanadium du type précipitation, les liquides conservant une réactivité et une aptitude à l'écoulement libre suffisantes de l'électrode lors d'une opération de charge/décharge, et permettant une charge et une décharge efficaces d'un point de vue énergétique. Le liquide de matériau actif d'électrode négative de batterie comprend un liquide contenant un composé de vanadium acide et d'acide sulfurique, le liquide de matériau actif d'électrode négative de batterie étant caractérisé par l'utilisation d'une électrode en carbone qui contient du vanadium bivalent et trivalent et dans laquelle une largeur de demi-valeur d'un pic de diffraction 002 selon une analyse de diffraction des rayons X n'est pas supérieure à 2,5°, une pluralité d'ondes d'oxydation de vanadium bivalent étant détectées comme observées par un procédé de balayage de potentiel dans lequel, l'électrode et le liquide de matériau actif d'électrode négative de batterie étant maintenus immobiles, un potentiel est balayé depuis un potentiel sur le côté négatif de -0,1 V en se référant à un potentiel d'électrode à hydrogène standard vers le côté positif. 本発明は、特定のバナジウム濃度や硫酸水素根等の形になっている硫黄濃度に限定されることなく、特にバナジウムを高濃度とする場合においても、液中の錯体が沈殿型のバナジウム化合物に移行しにくく、自由な充放電操作下において十分な電極反応性及び流動性を維持し、安定かつエネルギー効率のよい充放電が可能になる電池負極活物質液及び電池正極活物質液並びにこれらの調製方法を提供することを課題とし、電池負極活物質液は、硫酸酸性バナジウム化合物を含有する液からなる電池負極活物質液であって、２価及び３価のバナジウムを含有し、Ｘ線回折分析における００２回折ピークの半値幅が２．５°以下である炭素電極を用い、該電極及び該電池負極活物質液を静止させて、標準水素電極電位基準で－０．１Ｖよりも卑側の電位から貴側に向けて電位を掃引する電位掃引法によって観察される２価のバナジウムの酸化波が複数検出されることを特徴とする。